Emerging Dual‐Channel Transition‐Metal‐Oxide Quasiaerogels by Self‐Embedded Templating. (19th February 2020) - Guo, Hele; Zhou, Jun; Li, Qianqian; Li, Yueming; Zong, Wei; Zhu, Jixin; Xu, Jingsan; Zhang, Chao; Liu, Tianxi
Abstract: The lack of precise control of particle sizes is the critical challenge in the assembly of 3D interconnected transition‐metal oxide (TMO) for newly‐emerging energy conversion devices. A self‐embedded templating strategy for preparing the TMO@carbon quasiaerogels (TMO@C‐QAs) is proposed. By mimicking an aerogel structure at a microscale, the TMO@C‐QA successfully assembles size‐controllable TMO nanoparticles into 3D interconnected structure with surface‐enriched carbon species. The morphological evolutions of intermediates verify that the self‐embedded Ostwald ripening templating approach is responsible for the dual‐channel TMO@C‐QA formation. The general self‐embedded templating strategy is easily extended to prepare various TMO@C‐QAs, including the Co3 O4 @C‐QA, Mn3 O4 @C‐QA, Fe2 O3 @C‐QA, and NiO@C‐QA. Benefiting from the unparalleled 3D interconnected network of aerogels, the Co3 O4 @C‐QA displays superior bifunctional catalytic activities for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER), as well as high specific capacity and excellent long‐term stability for lithium‐ion battery (LIB) anode. A proof‐of‐concept battery‐powered electrolyzer with Co3 O4 @C‐QA cathode and anode powered by a full LIB with Co3 O4 @C‐QA anode is presented. The battery‐powered electrolyzer made of the state‐of‐the‐art TMOs can exhibit great competitive advantages due to its supreme multifunctional energy conversion performance for future water electrolysis. Abstract : A self‐embedded templating strategy is proposed for preparing dual‐channel transition‐metal oxide@carbon quasiaerogels (TMO@C‐QAs). These can readily work as a highly active and durable oxygen evolution reaction/hydrogen evolution reaction bifunctional electrocatalyst for battery‐powered water electrolysis.